Proposal of an Analytical Model on Collaborative Learning Articles Published in The Last Five Years - Cardoni, Juliana (2023)
Research on the bibliographic review studies on collaborative learning at the university level published in the last five years, allows to verify an absence of systematic comparative analysis of explicit and exhaustive analytical criteria that enables ordering of the different contributions. Precisely, the objective of this work was to establish a referential analytical model that allows a clear systematization of the corpus of articles recovered in the period 2018-2022. To meet this objective, a bibliographic search was carried out in the databases: SciELO, RedALyC, Eric and Dialnet. 71 studies were recovered. In the first part of the manuscript, this corpus of research was analyzed based on the constructed analytical criteria or variables. In the second part, the variables of the proposed model were analyzed inclusively. Based on this systematization, 12 studies were selected that can be considered paradigmatic of the variables and classificatory modalities. In conclusion, the proposed analytical model allowed us to detect the existing diversity in the articles published in the last five years. Despite this great variety of research, the ordering of the articles according to classifying criteria makes it possible to elucidate certain patterns. Research in the last five years study the interactions that occur in the collaboration process, certain conditions under which collaborative learning is more efficient, and the effectiveness of certain strategies to support students' interactional, regulatory, and metacognitive processes.